Thirty-two years of research on information foraging theory: Evolution, key contributions and emerging directions - Williams Nwagwu (Malaysian Journal of Library and Information Science, 2024)
This paper examines the evolution and future directions of Information Foraging Theory (IFT) research over the past 32 years (1992–2023). The findings reveal a sustained interest in IFT, with an average of 14 publications per year, culminating in a total of 449 papers authored by 933 researchers. Key contributors such as Peter Pirolli and Margaret Burnett have significantly shaped the field. Initially rooted in cognitive psychology and human-computer interaction (HCI), IFT has since expanded its influence to domains including information science, organizational behaviour, and machine learning. Core concepts of IFT, such as information scent and information patches, have been empirically validated, reinforcing their importance in understanding user behaviour. Publication trends highlight a peak in research activity around 2012, followed by fluctuations and a recent resurgence. The prominence of conference papers reflects the dynamic and rapidly evolving nature of the field. Keyword analysis identifies research clusters focusing on human decision-making, user interfaces, information retrieval, visualization, social networking, and behavioural studies, demonstrating the interdisciplinary application of IFT. Emerging themes such as cognitive load, uncertainty, virtual reality, and big data point to promising new research directions. This overview underscores IFT’s significant contributions and ongoing relevance in understanding of human information-seeking behaviour and optimizing systems to meet user needs.